TRIM5α self-assembly and compartmentalization of the HIV-1 viral capsid - Alvin Yu (Nature Portfolio, 2020)
Tripartite-motif containing (TRIM) proteins modulate cellular responses to viral infection. Here the authors use molecular dynamics simulations to demonstrate that TRIM5α uses a two-dimensional lattice hopping mechanism to aggregate on the HIV capsid surface and initiate lattice growth.